Minutes of introductory meeting with the supplier of fire detection and fire protection system BRACU new campus project - Brac University (Brac University, 2023)
Minutes of the introductory meeting with the supplier of fire detection and fire protection system for BRACU new campus project, held on 10th March, 2020.